ANTIBACTERIAL ACTIVITY AND INHIBITION OF BIOFILM OF Hibiscus tiliaceus STEM BARK METHANOL EXTRACT TO Streptococcus mutans GROWTH - Lukaraja, Wati; Lessy, Widya; Seumahu, Cecilia Anna; Pesik, Anneke (Universitas Pattimura, 2020)
Dental caries is an infectious disease that occurs in the oral cavity preceded by the formation of dental plaque or biofilm. This study aims to examine the inhibition and biofilm inhibition of hibiscus tree bark extract (Hibiscus tiliaceus). The test methods used were Minimum Inhibitory Concentration (MIC) and Minimum Killing Concentration (MBC) while the analysis of biofilm inhibition used UV-VIS spectrophotometry at a wavelength of 580 nm with McFarlandII standard (6x108 CFU/ml). The results showed that the methanol extract of hibiscus bark at a small concentration of 0.5% could inhibit and kill Streptococcus mutans as indicated by the number of colonies that grew less with a value of 3.34 x 107 CFU/ml in colonies that grew at an extract concentration of 2. % and 1%. Biofilm inhibition is shown by the decreasing absorbance value due to the increased extract concentration so that less biofilm formation occurs.